Squash, Zucchini—Cucurbita pepo L. - James M. Stephens (EDIS, 2003)
This document provides an overview of zucchini squash (Cucurbita pepo L.), detailing its growing habits, physical characteristics, and cultural requirements in Florida. It describes various cultivars, their fruit shapes, colors, and plant structures, and offers guidance on planting, pollination, pest management, and harvesting. Zucchini is highlighted as a popular, easy-to-grow vegetable with nutritional benefits, commonly consumed raw or cooked. Original publication date May 1994.